2015
DOI: 10.1111/ejn.13108
|View full text |Cite
|
Sign up to set email alerts
|

Role of HSP70 in motoneuron survival after excitotoxic stress in a rat spinal cord injury model in vitro

Abstract: The outcome for gait recovery from paralysis due to spinal lesion remains uncertain even when damage is limited. One critical factor is the survival of motoneurons, which are very vulnerable cells. To clarify the early pathophysiological mechanisms of spinal damage, an in vitro injury model of the rat spinal cord caused by moderate excitotoxicity was used. With this preparation we investigated whether motoneuron survival was dependent on the expression of the neuroprotective protein HSP70. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…24, 25 Figures 5b and c show that, after TBOA or nicotine treatment, Hsp70 expression was unchanged compared with basal sham conditions. When nicotine and TBOA were co-applied, Hsp70 expression was significantly enhanced ( P =0.027 among groups; P <0.05 for sham versus nicotine + TBOA; n =5 brainstems).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…24, 25 Figures 5b and c show that, after TBOA or nicotine treatment, Hsp70 expression was unchanged compared with basal sham conditions. When nicotine and TBOA were co-applied, Hsp70 expression was significantly enhanced ( P =0.027 among groups; P <0.05 for sham versus nicotine + TBOA; n =5 brainstems).…”
Section: Resultsmentioning
confidence: 97%
“…In fact, protection of motoneurons from excitotoxicity depends to a large extent on the binding by Hsp70 of AIF, a mitochondrial factor released by metabolically damaged motoneurons. 24, 25 When, during excitotoxicity, Hsp70 expression is insufficient to bind AIF, the latter migrates to the cell nucleus and inactivates DNA. 31 We, therefore, studied immunohistochemical expression of AIF when TBOA was applied alone or together with nicotine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, higher levels of HSPs have been detected in the cerebrospinal liquid of dogs with spinal cord injury (Awad et al., ). In our former report (Shabbir et al., ) using an in vitro spinal cord model simulating the excitotoxic damage developing as an early consequence of spinal injury, we observed that motoneurons able to survive this insult usually expressed high levels of HSP70. Furthermore, pharmacological inhibition of HSP70 intensified neuronal losses, especially motoneuronal death (Shabbir et al., ).…”
Section: Introductionmentioning
confidence: 66%